Polymers with Upper Critical Solution Temperature in Aqueous Solution - Seuring, Jan; Agarwal, Seema (Macromolecular rapid communications., 2012)
This review focuses on polymers with upper critical solution temperature (UCST) in water or electrolyte solution and provides a detailed survey of the yet few existing examples. A guide for synthetic chemists for the design of novel UCST polymers is presented and possible handles to tune the phase transition temperature, sharpness of transition, hysteresis, and effectiveness of phase separation are discussed. This review tries to answer the question why polymers with UCST remained largely underrepresented in academic as well as applied research and what requirements have to be fulfilled to make these polymers suitable for the development of smart materials with a positive thermoresponse. Why are polymers with UCST in water underrepresented in academic and applied research? This review tries to answer this question. Furthermore, a guide for the synthesis of novel UCST polymers is presented and possible handles to tune the phase transition temperature, sharpness of transition, hysteresis, and effectiveness of phase separation are discussed.